SINERGI TATA RUANG TERHADAP PELAKSANAAN REDD+: STUDI KASUS DI KABUPATEN KATINGAN, KALIMANTAN TENGAH - Nugroho Adi Utomo; Santun R.P Sitorus (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2016)
One effort to mitigate climate change is by perform the REDD+, which are containing emission reduction activities from deforestation and land degradation, sustainable forest management, carbon stock enhancement, and forest conservation. Katingan District is located in the REDD+ Pilot Project Province, Central Kalimantan. This study aims to analyze pattern of changes in the use of forest land, inconsistency of existing land use, content of policies concerning of basic element and process of REDD+, preferences of stakeholder to emerging REDD+ initiatives, and to formulate improvement of RTRW. The study was using Analyses of change andinconsistencies land use, Analytical Hierarchy Process, and descriptive analyses. The result of the study was forest land use was 60.47% and change patterns of forest land use occurred from forest to shrub/open land turned into plantation, agriculture and settlement. Analyses of inconsistencies land use indicated small value of inconsistency. While basic element and process of REDD+ contained in regional planning document; and stakeholders interested in the REDD+ initiative for direct benefit. Therefore, REDD+ initiatives possible to be implemented with some improvements in RTRW, through synchronization of REDD+ initiatives, and space allocation for REDD+ initiatives should be placed in protected areas and partially in cultivated areas.